[quotation] On the Information Society - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
On the Information Society: 'We need to develop applications, products and services which meet the specific needs of women. How can we, for example, help the great majority of women who work in the informal sector and in agriculture to benefit from...